PERSEPSI SISWA TERHADAP PEMBELAJARAN BAHASA INDONESIA DARING PADA MASA PANDEMI COVID-19 - Purwanto (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
This study aims to determine students’ perceptions of learning Indonesian Language online during the Covid-19 pandemic. This study used a quantitative descriptive analysis method with a research tool in the form of a questionnaire distributed online using Google Form. The number of samples in this study were 40 grade 8B students who took online learning during the Covid-19 pandemic. The results showed that 100% of grade 8B students of SMP Negeri 44 Surabaya completed online learning in the even semester of the 2020/2021 academic year. The most popular online media for students during online learning are Google Classroom (40.5%), WhatsApp (30.5%), Zoom (19%) and Microsoft Teams (10%). Even so, the majority of students, 85%, prefer offline or face-to-face learning to online learning.